Anti-inflammation effect of Qingchang suppository in ulcerative colitis through JAK2/STAT3 signaling pathway in vitro and in vivo. (10th February 2021) - Yu, Tianyuan; Li, Zicheng; Xu, Liwei; Yang, Ming; Zhou, Xin
Abstract: Ethnopharmacological relevance: Qingchang Suppository (QCS) is a Traditional Chinese Medicine formula (TCM) for Ulcerative Colitis (UC), which has been used for the treatment of UC for more than 30 years with therapeutic effect. This formula is optimized from a classic formula called "Qingdai San". Although some experiments have shown QCS effective for UC, its mechanism on UC is still unclear and needs to be clarified. Aim of the study: To investigate the usage of QCS in our hospital, clarify the main compounds in QCS and their anti-inflammation effect both in vivo and in vitro. Materials and methods: Prescription analysis was performed in the clinical department and pharmacology network prediction was predicted for relative signal pathways. 2, 4, 6-Trinitrobenzenesulfonic acid (TNBS)-induced colitis rats and Lipopolysaccharide (LPS)-induced Caco-2 cell as an inflammatory model were used to evaluate the effect of QCS. Results: QCS and its herbs were associated with inflammatory and immunological diseases. QCS and its ingredients showed little toxicity on Caco-2 cell and could down-regulate the level of Interleukin-6 (IL-6) and expression of signal transducer and activator of transcription 3 (P-STAT3 Tyr705) in LPS-induced Caco-2 cell. In an animal experiment, QCS and its ingredients (indigo and gallic acid) could alleviate the symptoms of TNBS-induced colitis of rats, significantly decrease pro-inflammatory factors and anti-inflammatory factors as well as inhibit the expressions of P-STAT3 and Tyr705. Conclusion: QCS and its components could improve UC by anti-inflammation. JAK2/STAT3 pathway might be the possible signaling pathway. Graphical abstract: Image 1